(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
The present article examines the theoretical foundations and methodological principles of linguopoetic analysis of literary texts. Literary discourse is characterized by complex linguistic structures through which objective reality is artistically reconstructed by means of imagery and aesthetic expression. The study emphasizes that the language of fiction serves as the primary distinguishing feature separating literary texts from other functional styles. Drawing on classical and modern linguistic theories, including the views of Aristotle, F. de Saussure, Goethe, and A. Alonso, the article highlights the interdisciplinary nature of linguopoetics at the intersection of linguistics and literary studies. Particular attention is paid to paradigmatic and syntagmatic word choice, stylistic markedness, graphic devices, and deviations from linguistic norms as tools for creating poetic meaning. The research also considers the role of idiomatic, pragmatic, and linguocultural features in revealing artistic imagery and character portrayal. Furthermore, the article outlines the contribution of Eastern linguistic and philosophical traditions to the development of text interpretation and word aesthetics. The findings demonstrate that linguopoetic analysis provides an effective framework for uncovering the aesthetic, semantic, and expressive potential of literary texts, thereby deepening the understanding of artistic language and its communicative functions.